Exploring Multidimensional View of Intellectual Capital and Business Ethics on Organizational Performance by Using Bootstrapping Method: Evidence from Pakistani Pharmaceutical Industry - Rizwan Raheem Ahmed; Jolita Vveinhardt; Dalia Streimikiene (Montenegrin Journal of Economics)
The objective of this research is to examine the effect of business ethics (BE) and intellectual capital (IC) on the organizational performance (OP). In order to run this study, a conceptual model was designed based on the literature review, and the employees of the knowledge-based organization in pharmaceutical sector were surveyed using a closed-ended questionnaire. Modern successful and thriving organizations are those that create IC and convert it into applicable methods to improve their activities and performance within the boundaries of BE. This research is exploratory and quantitative in nature: 400 responses were directly gathered from the employees of the pharmaceutical industry through five-scaled questionnaire. This research examined the direct and indirect effect of BE and IC on the OP. Structural equation modeling (SEM), descriptive statistics, correlation, multiple regression techniques were used to analyze the impact of IC and BE on the performance. Bootstrapping method is employed in order to test the mediating effect of variables. Two-step SEM was used to the models to regress the cause and effect relation. The findings depicted that there is a very significant effect on BE and IC in the performance of pharmaceutical organizations. General BE, ethics in finance, ethics in human resource management, and ethics in sales and marketing have direct and significant impact on the OP. Human capital, structural capital and relational capital have significant indirect (mediating) effect on the performance of the pharmaceutical industry. Finally, it has been concluded from the results of the research study that IC is the major contributor of the OP as a mediating variable with defined set of principles of BE in the pharmaceutical sector of Pakistan.